A case study of student perceptions of mental health services at three Maine community colleges - Stoldt, Tyler D. (My University, 2025)
The mental health needs of community college students have gained increasing attention, particularly in light of the exacerbating effects of the COVID-19 pandemic. While mental health services on college campuses have evolved, little research has explored how students perceive and engage with these resources within the unique environment of two-year institutions. The purpose of this qualitative case study was to develop an understanding of community college students’ perceptions of mental health services. The public information and the description provided by the counseling services administrator and program documents at three Maine community colleges were also collected to see if there was a relationship with the students’ perceptions. Data were collected through semi-structured interviews and documents and analyzed using Reflexive Thematic Analysis to identify shared patterns and themes. The theoretical framework for this study is Social Safety Theory, which emphasizes the importance of fostering inclusive and emotionally secure environments to mitigate social threats. Findings highlight the critical need for visible, accessible, and confidential mental health services, as well as the importance of addressing stress and isolation through proactive engagement. The study findings contribute to the understanding of mental health service delivery in community colleges and offer practical implications for enhancing student support systems in these institutions.
Keywords: Community college students; Mental health services; Social safety theory; Maine community colleges; Case study of Maine students